2014
DOI: 10.1177/0022034514543016
|View full text |Cite
|
Sign up to set email alerts
|

Smad2 Overexpression Reduces the Proliferation of the Junctional Epithelium

Abstract: The overexpression of the intracellular signaling molecule of the transforming growth factor-beta family (TGF-β) Smad2 was found to induce apoptosis and inhibit the proliferation rate of oral epithelial cells. Therefore, the aim of this study was to investigate in vivo the effect of Smad2 overexpression on the proliferation rate of the junctional epithelium (JE). Smad2 overexpression was driven by the cytokeratin 14 promoter (K14-Smad2) in transgenic mice. The K14-Smad2 mice were compared with wild-type (WT) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Furthermore, abrogation of TGF-βRII and Smad2 function using antisense ODN increased the tooth size and advanced the stage of tooth formation during mandibular morphogenesis, owing to increased cell proliferation of enamel organ (Chai et al 1999;Ito et al 2001). In addition, Smad2 overexpression reduced the level of the oral epithelium proliferation (Alotaibi et al 2014). Known as an inhibitor of TGF-β superfamily, Smad7 can antagonize the canonical TGF-β signaling by interfering with the recruitment of Smad2/3 and induce degradation of ALK5 (Lebrun et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, abrogation of TGF-βRII and Smad2 function using antisense ODN increased the tooth size and advanced the stage of tooth formation during mandibular morphogenesis, owing to increased cell proliferation of enamel organ (Chai et al 1999;Ito et al 2001). In addition, Smad2 overexpression reduced the level of the oral epithelium proliferation (Alotaibi et al 2014). Known as an inhibitor of TGF-β superfamily, Smad7 can antagonize the canonical TGF-β signaling by interfering with the recruitment of Smad2/3 and induce degradation of ALK5 (Lebrun et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number of apoptosis-positive cells was recently reported in the gingival junctional epithelium of smad2 transgenic mice [31] . Furthermore, the overexpression of smad2 reduced the proliferation of the junctional epithelium [32] and induced alveolar bone loss by up-regulating TNF-α and receptor activator of nuclear factor kappa-B ligand (RANKL) in transgenic mice [33] . On the other hand, we demonstrated that A. actinomycetemcomitans induced apoptosis in gingival epithelial cells by activating the TGF-β receptor I-smad2-caspase-3 signaling pathway [34] .…”
Section: Molecular Factors Associated With the Function Of The Junctimentioning
confidence: 99%
“…Smad2 and Smad3 were structurally very closely related and both were involved in signaling from TGF-β, Smad3 could form a complex together with Smad2 in order to regulate the target genes of TGF-βs. Over-expression of Smad2 inhibited the proliferation of junctional epithelium cells by down-regulating c-Myc and up-regulating p15 and p27 which leading to cellcycle arrest (Alotaibi et al 2014), and inhibited oral epithelial cell proliferation by increasing p15 and p21 (Shimoe et al 2014). However, Smad2 was not required for TGF-β-stimulated growth inhibition in hepatocytes (Ju et al 2006).…”
Section: Discussionmentioning
confidence: 99%